Atuação do intérprete educacional: interfaces entre os campos da educação e do discurso - Iriarte, Anne Caroline Santana (Universidade Federal de São Carlos, 2018)
The Libras (Brazilian Sign Language) / Portuguese translators and interpreters operate between linguistic and cultural borders. They are the subjects who mediate the interaction among deaf people and listeners. In the school context, however, their work is not restricted to this primary function, that is, it crosses this conception and goes through other ways which do not encompass just the linguistic and communicative aspects. The Educational Interpreter is called to also assume the educative function, as defended by Martins (2013), building a closer and more significant relationship with the deaf student than the one with the conducting teacher, since they share the same language. In this sense, it is necessary that teacher and interpreter work effectively in partnership, exchanging knowledge and experiences which aim to favor the deaf student’s learning and also collaborate to make student and teacher closer. This is a descriptive qualitative research which aims to analyze the Educational Interpreter operation at an inclusive nucleus school with bilingual project in the countryside of São Paulo state. For data collection, the observation instruments of everyday school were used, with registers on field notebook and semi-structured interview with the research subject. Data analysis was done from authors affiliated to Deaf Studies in Education and also Mikhail Bakhtin’s enunciative-discursive theory on the work Marxism and Philosophy of Language; both perspectives are articulated in order to reflect upon the Educational Interpreter practice, because they notice the professional’s activity as linguistic mediation and, beyond this function, they assume the professional is inserted in a sphere that calls for other functions, mainly the educational function, due to the genre and operation characteristic of the sphere itself. Thus, the results point at: a) the importance of a partnership between Educational Interpreter and conducting teacher when planning the methodologies to be used in classroom; b) the adoption of interpretative strategies with the use of image resources that help the deaf student in knowledge building and help the interpreter to have a higher quality performance; c) the importance of schools starting to give tests in Libras to deaf students, since it is through this language they acquire their knowledge; d) the context of a bilingual inclusive nucleus school favors the construction of a partnership between interpreter and teacher and also makes teacher and deaf student closer; e) the formation of the interpreter who works in the school must be specific, with two main lines: linguistic line, in order to acquire competences in translation and interpretation, and pedagogic line; f) Education Interpreters must be included in the offer of continuing formation by the educational systems. Given this, it is expected that this work contributes to broaden the discussions concerning this professional and to the promotion of a high quality teaching to deaf students.
Performance of the educational interpreter: interfaces between the fields of education and discourse
Keywords: Intérprete educacional; Função pedagógica; Formação específica; Educational interpreter; Pedagogic function; Specific formation; CIENCIAS HUMANAS